Does Special Educator Effectiveness Vary Depending on the Observation Instrument Used?. Issue 1 (10th September 2020) - Johnson, Evelyn S.; Crawford, Angela R.; Zheng, Yuzhu; Moylan, Laura A.
Abstract: In this study, we compared the results of 27 special education teachers' evaluations using two different observation instruments, the Framework for Teaching (FFT), and the Explicit Instruction observation protocol of the Recognizing Effective Special Education Teachers (RESET) observation system. Results indicate differences in the rank‐ordering of teachers depending on which instrument was used. Overall scores on RESET were higher on average than those on FFT. Item‐level analyses showed that across 125 correlations, 73 were significant, low‐moderate, and 52 were nonsignificant. Implications for research and practice are discussed.